Methodological considerations in establishing and maintaining longitudinal health workforce studies: Lessons learned from the WiSDOM cohort in South Africa - Laetitia C. Rispel; Prudence Ditlopo; Janine White; Duane Blaauw (Taylor & Francis Group, 2021)
Background Health workforce cohort studies are uncommon in low-and middle-income countries (LMICs), especially those in sub-Saharan Africa. Objective Describe the methodology and lessons learned from establishing and maintaining the WiSDOM (Wits longitudinal Study to Determine the Operation of the labour Market among its health professional graduates) health professional cohort study in South Africa. Methods WiSDOM is a prospective longitudinal cohort study that commenced in 2017. The cohort focuses on the eight professional groups of clinical associates, dentists, doctors, nurses, occupational therapists, oral hygienists, pharmacists and physiotherapists. Annual, electronic follow-up surveys have been conducted in 2018, 2019 and 2020 with informed consent. Key steps in establishing the WiSDOM cohort include consultation, communication and marketing, stakeholder feedback, resources and infrastructure. Retention strategies consist of an electronic database, detailed cohort contact information, cohort engagement, communication and feedback, short survey tools, and appropriate incentives. Results We obtained an overall response rate of 89.5% at baseline in 2017, 79.6% in 2018, 68.3% in 2019 and 72.8% in 2020. The largest decline in response rates is for medical doctors: 66.0% response rate in 2018, 53.2% in 2019 and 58.2% in 2020. However, for each of the three follow-up surveys, we have obtained response rates in excess of 80% for clinical associates, dentists, nurses, oral hygienists, pharmacists and physiotherapists. Since baseline, the outright refusals have remained very low at 4.7%. The multiple logistic regression analysis showed that self-identified race was the only significant socio-demographic difference between medical doctor respondents and non-respondents. Black African doctors and Indian doctors were 2.0 and 2.6 times more likely respectively to respond than White doctors (p < 0.05). Conclusion Other LMICs can learn from WiSDOM's lessons of establishing and maintaining a health professional cohort that aims to generate new knowledge for health system transformation.